DOES THE BETTER‐THAN‐AVERAGE EFFECT SHOW THAT PEOPLE ARE OVERCONFIDENT?: TWO EXPERIMENTS. Issue 2 (4th November 2014) - Benoît, Jean‐Pierre; Dubra, Juan; Moore, Don A.
Abstract: We conduct two experimental tests of the claim that people are overconfident, using new tests of overplacement that are based on a formal Bayesian model. Our two experiments, on easy quizzes, find that people overplace themselves. More precisely, we find apparently overconfident data that cannot be accounted for by a rational population of expected utility maximizers who care only about money. The finding represents new evidence of overconfidence that is robust to the Bayesian critique offered by Benoît and Dubra (Jean‐Pierre Benoît and Juan Dubra (2011). "Apparent Overconfidence." Econometrica, 79, 1591–1625). We discuss possible limitations of our results.